Chemical compositions of brown and green seaweed, and effects on nutrient digestibility in broiler chickens - Azizi, Mohammad Naeem; Loh, Teck Chwen; Foo, Hooi Ling; Akit, Henny; Wan Ibrahim, Wan Ahmad Izuddin; Shazali, Nurhazirah; Lim, Eric Teik Chung; Samsudin, Anjas Asmara @ Ab Hadi (Multidisciplinary Digital Publishing Institute, 2021)
This study aimed to analyse the nutritional properties, apparent ileal digestibility (AID) and apparent metabolisable energy (AME) of broiler chickens fed with brown seaweed (BS) and green seaweed (GS). Proximate analysis was performed to determine the nutrient composition of seaweed. The amino acids were determined using high-performance liquid chromatography (HPLC), and atomic absorption spectroscopy was used to determine the minerals content. The gross energy (GE) was determined using a fully automatic bomb calorimeter, and the AME value was calculated. Titanium dioxide (TiO2) was used as an indigestible marker to calculate the AID. A digestibility trial was conducted to investigate the effects of seaweeds on crude protein (CP), crude fibre (CF), ether extract (EE), dry matter (DM), organic matter (OM), amino acids (AA) and minerals digestibility, and AME on broiler chickens. Thirty-six broiler chickens were randomly distributed into two dietary treatment groups with six replicates and three birds per replicate. Results showed that brown and green seaweed was a source of macro and micronutrients. For the AME and AID of seaweed-based diets, the results showed that the AME value for BS and GS was 2894.13 and 2780.70 kcal/kg, respectively. The AID of BS and GS was 88.82% and 86.8% for EE, 82.03% and 80.6% for OM, 60.69% and 57.80% for CP, 48.56 and 44.02% for CF, and 17.97 and 19.40% for ash contents, respectively. Meanwhile, the AID of CP and CF was significantly higher for BS compared to the GS. Findings showed that the AID of various AA was 40.96 to 77.54%, and the AID of selected minerals (Ca, Na, K, Mg, Zn, Cu, Fe) for both BS and GS groups were above 90%.